2020
DOI: 10.1371/journal.pgen.1009005
|View full text |Cite
|
Sign up to set email alerts
|

Functional information from clinically-derived drug resistant forms of the Candida glabrata Pdr1 transcription factor

Abstract: Azole drugs are the most frequently used antifungal agents. The pathogenic yeast Candida glabrata acquires resistance to azole drugs via single amino acid substitution mutations eliciting a gain-of-function (GOF) hyperactive phenotype in the Pdr1 transcription factor. These GOF mutants constitutively drive high transcription of target genes such as the ATP-binding cassette transporter-encoding CDR1 locus. Previous characterization of Pdr1 has demonstrated that this factor is negatively controlled by the action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…S1, further confirming the resistance of the strains to fluconazole relative to the upc2A∆. As discussed above, the most common mechanism of fluconazole resistance is Pdr1 gain-of-function mutations that lead to increased expression of Cdr1, a putative fluconazole efflux pump (7,8). To determine if any of the 11 large colony isolates had increased Cdr1 expression, we analyzed the protein levels of Cdr1 protein in the suppressor strains by western blot (Fig.…”
Section: Experimental Laboratory Evolution Generates Suppressors Of Upc2a∆ Fluconazole Hypersusceptibilitysupporting
confidence: 54%
“…S1, further confirming the resistance of the strains to fluconazole relative to the upc2A∆. As discussed above, the most common mechanism of fluconazole resistance is Pdr1 gain-of-function mutations that lead to increased expression of Cdr1, a putative fluconazole efflux pump (7,8). To determine if any of the 11 large colony isolates had increased Cdr1 expression, we analyzed the protein levels of Cdr1 protein in the suppressor strains by western blot (Fig.…”
Section: Experimental Laboratory Evolution Generates Suppressors Of Upc2a∆ Fluconazole Hypersusceptibilitysupporting
confidence: 54%
“…Various reports have found that antifungal-resistant C. glabrata strains have mutations associated with the Pdr1 transcription factor and the overexpression of the ABC-type efflux pumps (ATP-Binding Cassette), mainly CDR1 and CDR2 ( Candida Drug Resistance) [ 8 , 118 , 119 , 120 ]. Such pumps can translocate small molecules to the outside of the cell and are regulated by the TAC1 transcription factor [ 121 , 122 ].…”
Section: Antifungal Resistance Of the C Glabrata Complexmentioning
confidence: 99%
“…Several mutations have been identified in the PDR1 zinc-cluster-containing transcription factor in the C. glabrata complex that favor the overexpression of the CDR1 , CDR2 , SNQ2, and PDH1 transporters, which are known to carry multiple drugs [ 117 , 118 , 119 , 120 , 123 ]. For example, Hou et al observed that 14 C. glabrata isolated strains with polymorphisms in PDR1 showed increased resistance to fluconazole (MIC ≥ 64 μg/mL) [ 124 ].…”
Section: Antifungal Resistance Of the C Glabrata Complexmentioning
confidence: 99%
“…Additionally, the reduced accumulation of Pdr1 in the presence of DM Erg11 supported the view that this mutant enzyme led to Pdr1 activation as evidenced by the lower steady-state levels of this transcription factor. Previously, we used the MET3 promoter to produce either wild-type or GOF Pdr1 proteins (28). The GOF proteins were found to be less stable than the corresponding wild-type factor.…”
Section: Increased Activation Of Pdr1 and Cdr1 Transcription Seen In Presence Of Gof Pdr1mentioning
confidence: 99%